Invoking spatial justice in urban mobility in Nairobi: A commuter’s perspective - Dorcas Nthoki Nyamai (European Journal of Spatial Development, 2023)
Justice in relation to mobility is invoked and performed in various ways. This is based on the premise that space not only contains resources that can be distributed but also consists of individuals who are highly mobile within that space, and whose perceptions play a pivotal role in shaping the concept of justice in relation to mobility. Mobility is an enabler for access to resources and opportunities that are spatially dispersed. However, in Nairobi, the injustices prevalent in the mobility landscape enable access for some users while restricting it for others. This presents a notable way in which justice in relation to urban mobility unfolds. Through sixty-five in-depth interviews with commuters in Nairobi, this research reveals that individuals’ everyday experiences not only present a multifaceted connection between justice and mobility but also shape which specific facet of justice takes precedence in one’s consciousness. Notably, affordability of public transit, police misconduct, safety of non-motorized users, neglect of traffic regulations and ensuing impunity are some of the prominent ways in which injustices in mobility are made manifest. Furthermore, the unclear laws and regulations that govern road use sustain a system riddled with uncertainties and injustices. Promoting transparency, creating platforms for citizen engagement, integrating technology in traffic management system, fostering a culture of accountability, and enhancing public awareness of regulations and mobility rights through comprehensive civic education represent some of the interventions and strategies that can be invoked to redress the injustices prevalent in Nairobi’s mobility landscape.